Hubungan Body Image Dan Tingkat Kecukupan Zat Gizi Makro Dengan Status Gizi Pada Remaja Putri SMA Negeri 3 Suarabaya - Nurul Mawaddah; Lailatul Muniroh (Jurnal Keperawatan Muhammadiyah, 2019)
ABSTRACTThe age of adolescence is a time of when  a development of personal identity, self-esteem and body image perception, as well as the awareness of psychosocial sexuality happen. Changes and alteration in body  shape and size of the adolescents could lead to the emmergence of a negative body image and  eating disorders among them. Factors that possible caused of nutritional problems in adolescents are the presence of body image and also the level of nutritional intake. The purpose of this study was to analyze the association between body image and the adequacy level of carbohydrate with the nutritional status in female adolescents of Senior High School 3 Surabaya. The research design was cross sectional design. The population in this research were 490  female students of  XI and XII grade of Senior High School 3 Surabaya SMA Negeri 3 Surabaya. The sample size were of 80 female students selected by Simple random sampling. The research variables were Body image was obtained by the Multi-dimensional Body Self Relations Questionnaire  (MBSRQ-AS) , the adequacy level of  macro nutrients was obtained by 2x24 hours food recall method, and nutritional status was determined by BMI / Age measurements.The results showed that the majority of respondents were satisfied with their body shape (86.3%), the adequacy level of carbohydrate was mostly in the “inadequate” category (56,3%), the adequacy level of energy was mostly in the “inadequate” category (58,8%), the adequacy level of protein was mostly in the “adequate” category (71,3%) and the adequacy level of fat was mostly “inadequate” category (57,5%). The correlation test stated that there is an association between body image and the nutritional status of female adolescents (p = 0,000). The result of this research showed that no correlation between nutrient intake of carbohydrates (p=0.353), energy (p=0.534), protein (p=0.978) and fat (p=0.814) with nutritional status. The conclusion from this study is a positive body image  supports a normal nutritional status in female adolescents.Keywords: Body image, the adequacy level of macro nutrients, nutritional status, and  female adolescent